Occupational Health and Safety, and Environmental management on the age of Fourth Industrial Revolution - Chalaris, Michail (Technium Business and Management, 2022)
The effective management of safety, health and environment in all workplaces has many benefits. These benefits include, for example, the improved overall wellbeing of the workforce, increased productivity, reduced work-related accidents, injuries and fatalities, and a positive public impression of the organization and its management. The paper highlights the importance of effectively managing occupational health and safety, and the environment during general industrial activities.